Work-rate analysis using the POWER (Periods of Work Efforts and Recoveries) System - O'Donoghue, P. G.; Hughes, M. G.; Rudkin, S.; Bloomfield, J.; Cairns, G.; Powell, S. (International Journal of Performance Analysis in Sport, 2005)
The POWER system is a work-rate analysis system that allows observers to enter periods of work and rest performed by players during matches. The data are processed to provide three sets of performance indicators relating to work-rate. Firstly, the frequency, mean duration and percentage match time spent performing work and rest are presented. Secondly, the number of bursts of 7 different duration classes and number of recoveries of 8 different duration classes are presented. The third type of output is a summary analysis of repeated work bouts. A repeated work bout is any period of 2 or more work bursts separated by recoveries of less than 20s. Analysis of repeated work bouts gives a fuller indication of the intermittent nature work performed in individual and team games. The use of the kappa statistic to evaluate reliability of work-rate is recommended when using the POWER system. Kappa was shown to have a greater degree of construct validity for reliability assessment than percentage error, chi square and Pearson's r. The POWER system has been demonstrated to be capable of being used objectively and reliably for the analysis of work-rate in soccer.